2022
DOI: 10.1002/smll.202205168
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Engineering of Sn‐Based Catalysts for Efficient Electrochemical CO2 Reduction

Abstract: safe limit 350 ppm), [7] which increased to 414 ppm in 2020, [3,8] with an annual growth rate of ≈1.57 ppm. This value will probably reach 570 ppm by 2100 without proper regulation. [9] Such high concentration of CO 2 in the atmosphere have triggered a series of ecological and environmental issues, including climate change, glacier melting, and sea levels rising, [7,8,10,11] which threaten the sustainable development of humans. Significant endeavors have been devoted to impede the increase of CO 2 concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 167 publications
1
22
0
Order By: Relevance
“…The results of XPS studies conducted on the tin before and after CO 2 reduction gave similar outcomes; they all showed that SnO structures became the dominant phase after reduction [61,62] . Further, in‐situ and operando analyses have also proved that tin oxide and metallic tin co‐exist (SnO x /Sn) on the surface of the tin‐based electrocatalysts during reduction rather than the metallic tin (Sn 0 ) [6,35,50,55–57,61–66] . Based on the mentioned studies and the obtained Raman analysis in this work, the improved formate selectivity over An−Sn NW electrodes results from the mixed oxide structure, the main catalytic layer for CO 2 reduction.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…The results of XPS studies conducted on the tin before and after CO 2 reduction gave similar outcomes; they all showed that SnO structures became the dominant phase after reduction [61,62] . Further, in‐situ and operando analyses have also proved that tin oxide and metallic tin co‐exist (SnO x /Sn) on the surface of the tin‐based electrocatalysts during reduction rather than the metallic tin (Sn 0 ) [6,35,50,55–57,61–66] . Based on the mentioned studies and the obtained Raman analysis in this work, the improved formate selectivity over An−Sn NW electrodes results from the mixed oxide structure, the main catalytic layer for CO 2 reduction.…”
Section: Resultssupporting
confidence: 68%
“…In addition, we have also anodically oxidized the tin nanowires to benefit from improved catalytic performance [41] and increased surface area [42–46] . Compared to other studies in the literature on tin‐based nanowires, [25,26,34,35] our work put a difference by introducing the production of the catalyst via the AAO template followed by anodic oxidation. Moreover, our electrocatalyst does not require to be deposited on any substrate (carbon paper, GDL, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemical CO 2 reduction reaction (CO 2 RR) is regarded as a sustainable and safe technology that combines CO 2 capture and direct conversion to produce low-carbon chemicals and fuels. Recent techno-economic analysis manifests that formate, among the various CO 2 RR products, is practically viable and commercially profitable in industrial applications owing to the relatively low activation potential needs. , It has been demonstrated that various metals and their derivatives could convert CO 2 into formate which could be readily incorporated to produce value-added chemicals. , For instance, Sn-based materials are attractive catalysts for the CO 2 RR to formate in terms of their earth-abundant merits. Unfortunately, it remains challenging to realize high selectivity owing to the inappropriate binding energy with intermediates and severe hydrogen evolution reaction (HER) . Furthermore, the poor electrical conductivity of monometallic Sn-based materials leads to undesirable electrocatalytic activity. , …”
Section: Introductionmentioning
confidence: 99%
“…As formate is a kind of important industrial feedstock and hydrogen carrier in energy industry, it is considered as one of the promising products in the eCO 2 RR process. [5][6][7][8] Hereby, it is urgent to develop more high performance electrocatalyst to boost the CO 2 -to-formate reduction. Heretofore, metal-based catalysts (such as Bi, [9][10][11][12] Sn, [13][14][15] In, [16][17][18] Pb, [19,20] and Pd, [21][22][23] ) present excellent formate selectivity in the eCO 2 RR process.…”
Section: Introductionmentioning
confidence: 99%